Seismic Soil-Structure Interaction Analysis of Isolated Nuclear Power Plants in Frequency Domain - Zhiguang Zhou; Xiaodong Wei (Shock and Vibration)
One important aspect of applying seismic isolation to Nuclear Power Plants (NPPs) is that the complex interactions of flexible soil, flexible isolators, and stiff structures require careful investigation. In this paper, a NPP model was used to investigate the effects of SSI and the effects of changing soil and isolator properties on seismic response of an isolated NPP. The following aspects are considered in the study: horizontal excitation and vertical excitation; linear and equivalent-linear models of the isolators; scaling of the shear modulus of the soil profile model; and scaling of the horizontal equivalent stiffness of the isolators. It was found that Pseudospectral Acceleration (PSA) in the nuclear structure at the frequencies near the natural frequency of the structure increase with elevation, and the difference between the in-structure response spectral acceleration with and without SSI effects is concentrated at the frequencies near the natural frequencies of the superstructure. It is also found that the linear SSI analysis underestimates the in-structure response of the nuclear structures compared to the equivalent-linear SSI analyses, and the soil profile properties directly affect the effectiveness of the isolation system.